The Potential Escalation of Strategic Partnership Conflicts in the Indo-Pacific Region from the AUKUS Trilateral Defense Pact - Edwina, Yodia Adriatami; Edwina, Yossica Ariatami (UI Scholars Hub, 2025)
The aggressiveness demonstrated by China in the South China Sea has caused instability and tension in military conflicts within the Indo-Pacific region. This aggressiveness was specifically demonstrated with the aim of controlling the sea in the region and considered a threat to maritime security, In an effort to balance the Indo-Pacific region against the aggressive attitude of China, the Trilateral Defense Pact agreement was made by Australia, United Kingdom, and United States. Despite the presented advantages associated with the effort, it is important to state that the agreement has raised concerns in Indonesia regarding its implications for maritime stability and the broader regional security landscape. Therefore, this study aims to thoroughly examine the probability of conflict escalation arising from the AUKUS Defense Pact. In order to achieve the stated objective, a descriptive analysis of normative publications was carried out using a literature review with a case-study approach. The study included a comprehensive examination of the developments that occurred in the Indo-Pacific region with a specific focus on the influence of the AUKUS Defense Pact. The obtained results showed that the AUKUS defense partnership agreement led to increased concerns among Indo-Pacific nations regarding national security. Regardless of the fact that the AUKUS aims to counterbalance the aggressive dominance of China, Indonesia has responded strategically by enhancing its maritime security efforts to maintain sovereignty.